Mangosteen Pericarp and Its Bioactive Xanthones: Potential Therapeutic Value in Alzheimer’s Disease, Parkinson’s Disease, and Depression with Pharmacokinetic and Safety Profiles - Ha Thi Thu Do (International Journal of Molecular Sciences, 2020)
Alzheimer’s disease (AD), Parkinson’s disease (PD), and depression are growing burdens for society globally, partly due to a lack of effective treatments. Mangosteen (Garcinia mangostana L.,) pericarp (MP) and its xanthones may provide therapeutic advantages for these disorders. In this review, we discuss potential therapeutic value of MP-derived agents in AD, PD, and depression with their pharmacokinetic and safety profiles. MP-derived agents have shown multifunctional effects including neuroprotective, antioxidant, and anti-neuroinflammatory actions. In addition, they target specific disease pathologies, such as amyloid beta production and deposition as well as cholinergic dysfunction in AD; α-synuclein aggregation in PD; and modulation of monoamine disturbance in depression. Particularly, the xanthone derivatives, including α-mangostin and γ-mangostin, exhibit potent pharmacological actions. However, low oral bioavailability and poor brain penetration may limit their therapeutic applications. These challenges can be overcome in part by administering as a form of MP extract (MPE) or using specific carrier systems. MPE and α-mangostin are generally safe and well-tolerated in animals. Furthermore, mangosteen-based products are safe for humans. Therefore, MPE and its bioactive xanthones are promising candidates for the treatment of AD, PD, and depression. Further studies including clinical trials are essential to decipher their efficacy, and pharmacokinetic and safety profiles in these disorders.